PENDIDIKAN KETAATAN BERIBADAH DAN AKTUALISASINYA DI SD AL-ISLAM YOGYAKARTA - Muhammad Idris Maas Zaid; Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
Education is a process in the formation of value elements through an approach so that values ​​are embedded in students who are expected to grow in the actualization of their worship values. Based on the results of the study it is known that not all students are obedient in worship. This is evident that only a few students are obedient in carrying out worship both at school and at home. This research is a descriptive qualitative research using a case study approach to 8 informants at SD AL-ISLAM Yogyakarta. Data collection was carried out by conducting observations, interviews, and documentation. Informants in this study were several fifth grade students, teachers, and the principal of SD AL-ISLAM Yogyakarta. The results of this study are; The actualization of worship observance at SD AL-ISLAM Yogyakarta is going well in the school environment. Meanwhile, in the home environment, students in their actualization have not run fully. Actualization of the observance of worship that is implemented at SD AL-ISLAM Yogyakarta is the activity of praying dhuha in congregation, praying fardhu in congregation, reading the Koran, memorizing the Koran, mabit (Tahajjut-and reading Al-Ma'sturat). That in the realm of education it is not only teaching and learning (transfer of knowledge), but how to instill it in students by involving aspects of knowledge about goodness (moral knowing), which directs desire or love (moral feeling), from that love will direct how to do good or called (moral action).